Cultura e relações de trabalho na fazenda Santa Cruz - município de Araguari - MG (1985 - 2005) - Fernandes, Vanusa Alves Viana (2005)
This research tends to understand the social and employment relations established between migrants from both Brazilian northeast and Parana and the proprietors of the Santa Cruz Farm - Araguari City, MG, from 1985 until 2005. Maize (corn), soy and coffee are cultivated in the related farm based in work wage-earning relations, however this research is mainly focused on the employment relations established in the tomato culture. I tried to understand the reasons of the migration, the preference for migrant workers and the transformations suffered with the changes in the work relations, which passed through three stages: partnership, pseudo waging and waging. Along with these stages, great changes in these workers´ lives occurred. These workers´ experiences, lived in the crop field, and the relations established in the city during this period, show us all about their struggle in searching for better life conditions, as well as the transformations and interactions of these workers´ ways of living.